Diversity and physiognomic structure at two riparian forest fragments associated toward dry ecosystems at the Colombian Caribbean (Montes de María - Sucre) - Luna-Blanco, Cindy P.; Álvarez-Pérez, Pedro J.; Gómez, Jorge Mercado (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Riparian forests are unexplored ecosystems within the tropical dry forest, and therefore little it’s unknown about its diversity and conservation. Herein we analyzed the diversity and physiognomic structure of the woody plants using RAP transects in two forest fragments (Bremen and El Principio) in the Montes de María (Sucre, Colombia). The families (IVIF) and species (IVI) highest importance values ​​were calculated; further, we established the relationships between the individual number and growth habits, altimetric class, diameter class. Further, basal area and diameter classes relationships also was calculated. Likewise, effective numbers of species alpha and beta diversity were calculated. A total of 75 species, 29 families and 67 genera were found. Fabaceae, Sapindaceae, Apocynaceae, Bignoniaceae, Malvaceae and Arecaceae are the richest families. According the IVIF and IVI outcomes Acanthaceae and Bravaisia ​​integerrima are family and species with the highest value of importance. Tress is the most important growth habit and according to the distribution by diametric diameter and height classes, the largest number of individuals are accumulated towards the lower classes, suggesting a disturbance vegetation mainly represented by juveniles. Diversity outcomes shows non-difference between Bremen and El Principio vegetation suggesting the same community. Our results allow suggest that the study areas have some successional vegetation degree, consequence of human disturbance, changing the structure and diversity of Bremen and El Principio.